Luther and the girls: religious denomination and the female education gap in 19th century Prussia - Sascha O. Becker; Ludger Wößmann (Institute for the Study of Labor (IZA), 2008)
Martin Luther urged each town to have a girls' school so that girls would learn to read the Gospel, evoking a surge of building girls' schools in Protestant areas. Using county- and town-level data from the first Prussian census of 1816, we show that a larger share of Protestants decreased the gender gap in basic education. This result holds when using only the exogenous variation in Protestantism due to a county's or town's distance to Wittenberg, the birthplace of the Reformation. Similar results are found for the gender gap in literacy among the adult population in 1871.
urn:nbn:de:101:1-20081127666
Keywords: I21; 330; Gender gap; education; Protestantism; Frauenbildung; Protestantismus; Geschlechterdiskriminierung; Bildungschancen; Preußen